2020
DOI: 10.1002/jbmr.4417
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Bone Health and Outcomes in the United States

Abstract: Osteoporosis is a bone disease classified by deterioration of bone microarchitecture and decreased bone strength, thereby increasing subsequent risk of fracture. In the United States, approximately 54 million adults aged 50 years and older have osteoporosis or are at risk due to low bone mass. Osteoporosis has long been viewed as a chronic health condition affecting primarily non‐Hispanic white (NHW) women; however, emerging evidence indicates racial and ethnic disparities in bone outcomes and osteoporosis man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 119 publications
(220 reference statements)
5
45
0
Order By: Relevance
“…A cohort study from China reported a positive association between pro-inflammatory diets and an increase in the long-term risk of OP in older Chinese women ( 22 ). Consistent with a previous study, the above studies proved that bone mineral density differs with race, ethnic group, and diet ( 23 ). Therefore, determining the association between OP and modified dietary inflammatory index (MDII) might provide information for the prevention and treatment of OP among different races.…”
Section: Introductionsupporting
confidence: 92%
“…A cohort study from China reported a positive association between pro-inflammatory diets and an increase in the long-term risk of OP in older Chinese women ( 22 ). Consistent with a previous study, the above studies proved that bone mineral density differs with race, ethnic group, and diet ( 23 ). Therefore, determining the association between OP and modified dietary inflammatory index (MDII) might provide information for the prevention and treatment of OP among different races.…”
Section: Introductionsupporting
confidence: 92%
“…It is widely believed that menopause and aging lead to bone loss ( 21 23 ). The white race is considered an established risk factor for OP ( 24 , 25 ). Calcium and vitamin D are two trace elements that affect bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between age, sex, race/ethnicity, and thyroid function, and their relationship between clinical outcomes, is made more complex by potential differences in the “normal” ranges of thyroid function between different sociodemographic groups ( 100 ). Furthermore, a large body of investigative work has been dedicated to defining and measuring sociodemographic and racial/ethnic disparities in clinical outcomes relevant to hypothyroidism, including cardiovascular morbidity/mortality and bone health ( 101 103 ). While there is no expectation that changes in thyroid hormone prescribing alone would ameliorate these disparities, any future studies examining sociodemographic disparities in clinical outcomes in the hypothyroid population would have to be interpreted within the context of these baseline differences.…”
Section: Sociodemographic Disparities In Clinical Outcomesmentioning
confidence: 99%